Growth prospects, the natural interest rate, and monetary policy - Salomon Fiedler; Klaus-Jürgen Gern; Nils Jannsen; Maik H. Wolters (Kiel Institute for the World Economy (IfW), 2019)
The recovery from the Global Financial Crisis was characterized by sluggish output growth and by inflation remaining persistently below the inflation targets of central banks in many advanced economies despite an unprecedented monetary expansion. Ten years after the Global Financial Crisis, GDP remains below its pre-crisis trend in many economies and interest rates continue to be very low. This raises the question of whether low GDP growth and low interest rates are a temporary phenomenon or are due to a decline in long-run growth prospects (potential output growth) and equilibrium real interest rates (natural interest rate). Addressing this question is important for central banks for conducting monetary policy and adjusting their strategy. In this paper, the authors address this question based on a review of the literature and an evaluation of the most recent data and discuss implications for monetary policy.
Keywords: E31; E32; E43; E52; E58; 330; natural interest rate; potential output; output gap; monetary policy